A NOTE ON THE OCCURRENCE OF MATURE OILSARDINE, SARDINELLA LONGICEPS VAL., OFF MADRAS COAST - Gnanamuthu, J C; Girijavallabhan, K G (Indian Journal of Fisheries, 2011)
The occurrence of mature oilsardine, Sardinella longiceps, during January- March of 1978 in Madras waters is reported and its significance discussed. The size ranges of 5. longiceps in the different months of their occurrence are given